Convenient Solutions to an Inconvenient Truth : Ecosystem-based Approaches to Climate Change - World Bank (World Bank, 2012)
Global warming and changes in climate have already had observed impacts on natural ecosystems and species. Natural systems such as wetlands, mangroves, coral reefs, cloud forests, and Arctic and high-latitude ecosystems are especially vulnerable to climate-induced disturbances. However, enhanced protection and management of biological resources and habitats can mitigate the impacts and contribute to solutions as nations and communities strive to adapt to climate change. Biodiversity is the foundation and mainstay of agriculture, forests, and fisheries. Biological resources provide the raw materials for livelihoods, agriculture, medicines, trade, tourism, and industry. Forests, grasslands, freshwater, and marine and other natural ecosystems provide a range of services often not recognized in national economic accounts but vital to human welfare: regulation of water flows and water quality, flood control, pollination, decontamination, carbon sequestration, soil conservation, and nutrient and hydrological cycling. Current efforts to address climate change focus mainly on reducing greenhouse gas (GHG) emissions by adopting cleaner energy strategies and on reducing the vulnerability of communities at risk by improving infrastructure to meet new energy and water needs. This book offers a compelling argument for including ecosystem-based approaches to mitigation and adaptation as an essential pillar in national strategies to address climate change. Such ecosystem-based strategies can offer cost-effective, proven, and sustainable solutions that contribute to, and complement, other national and regional adaptation strategies.